2011
DOI: 10.3944/aott.2011.2537
|View full text |Cite
|
Sign up to set email alerts
|

Squamous cell carcinoma arising from chronic osteomyelitis

Abstract: Amputation appears to be an effective treatment method in squamous carcinoma secondary to chronic osteomyelitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 16 publications
2
19
0
Order By: Relevance
“…Despite these data, in the present study, tumors showed no signals of metastatic disease at the moment of diagnosis in 83.3% ( n  = 5) of patients. All six patients in the study by Alami et al 7 were staged as N0M0. In contrast, out of the seven patients in the study by Altay et al, 10 three were at the N0M0 stage; two, N1M0; one, N1M1; the other died prior to the staging.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite these data, in the present study, tumors showed no signals of metastatic disease at the moment of diagnosis in 83.3% ( n  = 5) of patients. All six patients in the study by Alami et al 7 were staged as N0M0. In contrast, out of the seven patients in the study by Altay et al, 10 three were at the N0M0 stage; two, N1M0; one, N1M1; the other died prior to the staging.…”
Section: Discussionmentioning
confidence: 99%
“…Only two articles were case series: one with six and another with seven patients 1, 7, 10. Therefore, this series is one of the first to analyze a series of patients diagnosed with malignant transformation in the context of chronic osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conversion of chronic osteomyelitis to squamous cell carcinoma is a relatively rare event that often occurs decades after the primary insult. Prevention and early clinical diagnosis can lead to limb salvage; however, once seeded, the customary treatment is amputation of the affected extremity [5]. Cancer recurrence is rare after amputation; however, proximal migration of the bony infection is common.…”
Section: Discussionmentioning
confidence: 99%